2009
DOI: 10.1517/17425240902967599
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the release kinetics through the control of the permeability of the layer-by-layer assembly: a review

Abstract: The layer-by-layer (LbL) self-assembly technique has emerged as a simple and versatile method for coating biological and non-biological templates for various biomedical applications. A promising avenue of this technique lies in the encapsulation of drugs and other biological substances for controlled release. Fundamental studies of LbL assembly on flat surfaces have provided a sound understanding of film deposition theory and its pertinence to ionic and molecular transport and diffusion through polyelectrolyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 86 publications
0
25
0
Order By: Relevance
“…PEI of nearly identical molecular weight PEI (MW = 10,000 Da) served as the control because it is a well studied polycation and has been used in a wide variety of biomedical applications. [12-13] There is no standardized procedure to determine a polycation's biocompatibility in vitro, so we chose four assays that can evaluate toxicity from different perspectives and at progressively more severe levels. We examined the effects of PAGS on cell membrane integrity using lactate dehydrogenase (LDH) assay, metabolic activity using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, apoptosis using caspase-3 assay, and cell viability using calcein AM and ethiduim homodimer-1 staining followed by fluorescence measurements (live/dead assay).…”
Section: Resultsmentioning
confidence: 99%
“…PEI of nearly identical molecular weight PEI (MW = 10,000 Da) served as the control because it is a well studied polycation and has been used in a wide variety of biomedical applications. [12-13] There is no standardized procedure to determine a polycation's biocompatibility in vitro, so we chose four assays that can evaluate toxicity from different perspectives and at progressively more severe levels. We examined the effects of PAGS on cell membrane integrity using lactate dehydrogenase (LDH) assay, metabolic activity using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, apoptosis using caspase-3 assay, and cell viability using calcein AM and ethiduim homodimer-1 staining followed by fluorescence measurements (live/dead assay).…”
Section: Resultsmentioning
confidence: 99%
“…The release kinetics of the PEM films is important for possible applications. It is known to be influenced by the polyelectrolyte properties (pKa, molecular weight) and the solvent conditions (pH, ionic strength) [74]. Electrochemically active PEMs offer the advantage that electrochemical stimulation can be used as a trigger for release that is neither dependent on the polyelectrolyte properties nor on the solvent conditions.…”
Section: Relevance To Biotechnologymentioning
confidence: 99%
“…Other reports have demonstrated that PEMs can be released from their substrates by changes in pH,27,33,35 the addition of metal ions,32 or by the physical peeling of hydrogen bonded films from low-energy surfaces 28. These and other past studies have demonstrated the versatility of layer-by-layer methods for the fabrication of freestanding and flexible membranes of potential utility in a broad range of applications such as sensing,2,11,25,30,37 the controlled administration of therapeutics,38 and the design of new filtration/separation media 29,39…”
Section: Introductionmentioning
confidence: 98%